Phonological Strategies in Eminem’s Songs: Assimilation and Elision Analysis - Deflorino Yolis; Ni Putu Cahyani Putri Utami (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
This study investigates the phonological strategies of assimilation and elision in Eminem’s rap performance, focusing on two songs: Not Alike and Lucky You. While elision and assimilation are common in casual or fast speech, their usage in rap is often strategic, supporting rapid articulation, rhythmic precision, and stylistic expressiveness. The research applies a qualitative descriptive method, using close auditory analysis and phonetic transcription to identify patterns of connected speech. The theoretical framework draws on Generative Phonology (Chomsky & Halle, 1968) and Connected Speech Phenomena (Roach, 2009), which are particularly relevant for understanding systematic sound variation in dynamic, performance-based contexts like rap. The analysis reveals frequent occurrences of /?/-elision in -ing words (e.g., thinkin’, runnin’) and the omission of /t/, /d/, and /ð/ in clusters, particularly in Not Alike, highlighting syllabic efficiency and metrical tightness. Assimilation, slightly more dominant in Lucky You, mainly occurs as nasal place assimilation and palatalization, enabling smoother transitions and faster delivery aligned with the beat. These findings demonstrate intentional usage of phonological simplification to enhance musical fluency and rhythmic control. This study illustrates how rap integrates linguistic and musical performance, offering insights into how classical phonological rules are creatively manipulated through rule ordering and surface variation. Beyond theoretical relevance, the findings have practical implications for pronunciation teaching, prosodic awareness, and performance linguistics. Future research could explore cross-artist comparisons or listener perception of such reduced forms in real-time processing.